An inframarginal approach to trade theory / [Edited by] Xiaokai Yang,...[et al.] - Yang, Xiaokaiedited
Inframarginal analysis represents a methodology that extends marginalanalysis, using non-classical mathematical programming, in efforts toinvestigate corner solutions and indivisibilities. As such thisapproach has been used to reintroduce classical insights regarding thedivision of labor and economic organization to the mainstream ofeconomic inquiry.